Corrigendum to “Surviving the Tide: Assessing Guiana dolphin persistence amidst growing threats in a protected estuary in South-eastern Brazil” [J. Nature Conserv. 82 (2024) 126713] - Inaê Guion de Almeida; Alexandre Reis Percequillo; Mario Manoel Rollo (Journal for Nature Conservation, 2024)

Surviving the Tide: Assessing Guiana dolphin persistence amidst growing threats in a protected estuary in South-eastern Brazil - Inaê Guion de Almeida; Alexandre Reis Percequillo; Mario Manoel Rollo (Journal for Nature Conservation, 2024)

Phylogenomics and species delimitation of an abundant and little-studied Amazonian forest spiny rat - Jeronymo Dalapicolla; Joyce Rodrigues do Prado; L. Lacey Knowles; Alexandre Reis Percequillo (Molecular Phylogenetics and Evolution, 2024)

Andean non‐volant small mammals: A dataset of community assemblages of non‐volant small mammals from the high Andes - Edgardo M. Rengifo; Jorge Brito; J. Pablo Jayat; Raisa Cairampoma; Agustina Novillo; Natali Hurtado; Ignacio Ferro; Cesar E. Medina; Alfonso Arguero; Sergio Solari; Jose Urquizo; Ariatna Villarreal; et al. (Ecology, 2022)
Information from diversity inventories was used to study patterns of biodiversity and species distribution, to identify potential priority areas for conservation, and to guide future sampling efforts. In this context, we compiled information on non‐volant small mammal communities from the high Andes (>2000 m). Here, we present an open source dataset containing information on diversity (species composition, number of individuals captured), inventory design (type of traps, sampling efforts), and environment (habitat) for both unpublished and published information. This study covers 630 mammalian communities, geographically distributed throughout the Andes in Venezuela, Colombia, Ecuador, Peru, Bolivia, Argentina, and Chile. We compiled a total of 26,412 individual records belonging to 240 species; the order with greatest number of records was Rodentia ( n = 25,319, 96.06%), followed by Didelphimorphia ( n = 373, 1.42%), Eulipotyphla ( n = 358, 1.36%) and Paucituberculata, ( n = 307, 1.16%). Andean non‐volant small mammal communities harbor a range from 1 to 17 species, with 93.06% of sites being composed of one to five species, 27.78% of sites with species richness varying from 6 to 10 species, and 4.17% sites composed of more than 10 species. Multiple sampling methods were used to survey non‐volant small mammals; the most representative methods were snap‐traps and Sherman traps, or a combination of both, in more than 81% of the studies. This data paper represents the first large dataset of faunal species inventories for the Andes. There are no copyright restrictions associated with the use of this dataset. Please cite this data paper when its data are used total or partially in research or teaching.

Chromosomal evolution of tribe Oryzomyini (Rodentia: Cricetidae: Sigmodontinae) - Camila do Nascimento Moreira; Alexandre Reis Percequillo; Malcolm Andrew Ferguson-Smith; Yatiyo Yonenaga-Yassuda; Karen Ventura (Mammalian Biology, 2022)

Functional connectivity in sympatric spiny rats reflects different dimensions of Amazonian forest‐association - Jeronymo Dalapicolla; Joyce Rodrigues do Prado; Alexandre Reis Percequillo; L. Lacey Knowles (Journal of Biogeography, 2021)
Aim Understanding how the landscape influences gene flow is important in explaining biodiversity, especially when co‐distributed taxa across heterogeneous landscapes exhibit species‐specific habitat associations. Here, we test predictions about the effects of forest‐type on population connectivity in two sympatric species of spiny rats that differ in their forest associations. Specifically, we evaluate the hypothesis that seasonal floodplain forests ( várzea ) provide linear connectivity, facilitating gene flow among individuals, while non‐flooded forests ( terra‐firme ) may diminish the functional connectivity. Location Western Amazon, South America. Taxon Proechimys simonsi (non‐flooded forests, terra‐firme ) and Proechimys steerei (seasonal floodplain forests, várzea ). Methods We analyse about 13,000 single nucleotide polymorphisms along with characterizations of landscape heterogeneity for two forest types to test for differences in the functional connectivity. Influence of the landscape and environmental variables are quantified using maximum‐likelihood population effect models to identify the relative importance of variables in explaining the gene flow. Results There are significant differences in functional connectivity between species. However, the genomic data does not support the conventional hypotheses of higher connectivity for inhabitants of várzea than those of terra‐firme . Stronger genetic structure in P. steerei than P. simonsi based on isolation by distance models suggests reduced gene flow in species associated with várzea forests. Isolation by resistance reinforces that wetland habitats inhibit and promote the functional connectivity in P. simonsi and P. steerei , respectively, although large distances along the rivers can prevent gene flow in P. steerei . Main conclusion Interpreting differences between connectivity in taxa apparent from genetic analyses through the lens of a single dimension of Amazonian heterogeneity—that is, forest type—may be an oversimplification. Our statistical modelling and fit of the data to different models points to specific environmental and habitat differences between the ecological divergent spiny rat species that may contribute to differences in the genetic structure of these sympatric taxa.

Systematics of Brucepattersonius Hershkovitz, 1998 (Rodentia, Sigmodontinae): molecular species delimitation and morphological analyses suggest an overestimation in species diversity - Edson Fiedler Abreu; Diego Marques Henriques Jung; Alexandre Uarth Christoff; Victor Hugo Valiati; Sharon A. Jansa; Alexandre Reis Percequillo (Systematics and Biodiversity, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Bottom-up effect: a rodent outbreak following the bamboo blooming in a Neotropical rainforest - Ricardo Siqueira Bovendorp; Neander Marcel Heming; Alexandre Reis Percequillo (Mammal Research, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Systematic Studies of the Genus Aegialomys Weksler et al., 2006 (Rodentia: Cricetidae: Sigmodontinae): Geographic Variation, Species Delimitation, and Biogeography - Joyce Rodrigues do Prado; Alexandre Reis Percequillo (Journal of Mammalian Evolution, 2018)

Connectivity maintain mammal assemblages functional diversity within agricultural and fragmented landscapes - Marcelo Magioli; Katia Maria Paschoaletto Micchi de Ferraz; Eleonore Zulnara Freire Setz; Alexandre Reis Percequillo; Michelle Viviane de Sá Santos Rondon; Vanessa Villanova Kuhnen; Mariana Cristina da Silva Canhoto; Karen Evelyn Almeida dos Santos; Claudia Zukeran Kanda; Gabriela de Lima Fregonezi; Helena Alves do Prado; Mitra Katherina Ferreira; et al. (European Journal of Wildlife Research, 2016)

Ticks (Acari: Ixodidae) identified from prey–predator interactions via faecal analysis of Brazilian wild carnivores - Thiago F. Martins; Thaís R. Diniz-Reis; Gustavo S. Libardi; Alexandre R. Percequillo; Luciano M. Verdade; Eliana R. Matushima; Marcelo B. Labruna (Experimental and Applied Acarology, 2015)